Exploring the Dynamics of Interdisciplinary Palliative Care Teams in Providing Psychosocial Care: "Everybody Thinks that Everybody Can Do It and They Can't" - O'Connor, Moira; Fisher, C. (Mary Ann Liebert, Inc Publishers, 2010)
Background: There has recently been a call for an analysis of the way in which professionals see their role andstatus in the context of palliative care and the interdisciplinary team. This is particularly salient in the provisionof psychosocial care.Method: This study qualitatively explored team members’ perceptions and experiences of team dynamics. An indepthqualitative research design was adopted using semistructured interviews and was guided by a socialconstructivist framework. Seven palliative care team members were recruited from across three palliative caresites. Two palliative care nurses, a palliative care medical specialist, a consultant psychiatrist, a social worker, acounselor, and an occupational therapist comprised our prototypical interdisciplinary team. Analysis wasconducted using a method of constant comparison.Results: Two major themes emerged from our research: ‘‘Lack of clear role boundaries’’ and ‘‘Strategies formaintenance of role boundaries,’’ which included: ‘‘Claiming access to specialist expertise and knowledge’’ and‘‘Minimizing the knowledge of other professions and professionals.’’ It is argued that effective team functioningcan be enhanced through the development of interdisciplinary team training programs and policies, resourcesand structures that provide support for the interdisciplinary team model.